Atmospheric plasma-sprayed BaZr0.1Ce0.7Y0.1Yb0.1O3−δ (BZCYYb) electrolyte membranes for intermediate-temperature solid oxide fuel cells. Issue 16 (December 2016) - Sun, Haibin; Zhang, Shanlin; Li, Chengxin; Rainwater, Ben; Liu, Yuchen; Zhang, Lei; Zhang, Yujun; Li, Changjiu; Liu, Meilin
Abstract: The high co-sintering temperature of BZCYYb electrolyte membranes supported by anode substrates usually causes a series of problems including undesirable electrolyte-anode reactions/diffusion and Ba-evaporation, posing a challenge for seeking alternative fabrication approaches. In this study, BZCYYb electrolyte membranes supported by anode substrates are fabricated by a large-scale and cost-effective atmospheric plasma spraying (APS) process. The 25 µm thick BZCYYb membrane has negligible electrolyte-anode reactions/diffusion due to the APS process free of high-temperature co-firing. The Ba-evaporation problem is also resolved during APS process because of the adoption of large-grained BZCYYb feedstock powders. After 15 cycles of post-densification treatment by infiltrating, the plasma-sprayed BZCYYb membrane is dense enough for electrolyte application. The single cell based on dense plasma-sprayed BZCYYb electrolyte membrane shows a peak power density of 0.35 W cm −2 at 750 °C using 3 vol% humidified H2 as fuel and ambient air as oxidant.